Review Literatur : Pengaruh Konsentrasi Garam terhadap Hasil Fermentasi Brassica juncea L. untuk Pembuatan Kimchi - Handayani, Ida (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Kimchi is a traditional Korean food, made from fermented pickled vegetables mixed with spicy seasonings. Vegetables commonly used in making kimchi are Brassica juncea L. Brassica juncea L. which is soaked or salted for several hours, then washed and seasoned with a mixture of krill shrimp, fish sauce, garlic, ginger and red chili powder. Due to fermentation, kimchi has a sour taste like pickles. The focus of this article is to examine the effect of salt concentration on the fermentation yield of Brassica juncea L. for making kimchi. The method used is literature study. The literature used is national journals published in the last 10 years. Literature searches were carried out through the Google Scholar search engine, and several national journal websites online.